Progress with the ITER project activity in Russia. (19th June 2015) - Krasilnikov, A.V.; Abdyuhanov, I.M.; Aleksandrov, E.V.; Alekseev, A.G.; Amosov, V.N.; Antonov, N.V.; Arkhipov, N.I.; Burdakov, A.V.; Chugunov, I.N.; Denisov, G.G.; Gervash, A.A.; Ivantsivskiy, M.V.; et al.
Abstract: Due to the development of the ITER project, the requirements of the technical parameters of the ITER systems were more precisely and practically determined to be at higher levels. The essential increase of the ITER system characteristics happened recently. A number of prototypes were manufactured and tests were carried out. The results of the development and manufacture of 25 ITER systems, subject to the Russian Federation's obligations in the ITER project, are described.